Transcanal endoscopic management of isolated congenital middle ear malformations. (3rd January 2023) - Shi, Licai; Chen, Shuainan; Li, Rujie; Huang, Yideng
Abstract: Background: A few studies have reported transcanal endoscopic management of isolated congenital middle ear malformations (CMEMs). Objective: The purpose of this study is to describe our surgical experience in endoscopic ear surgery for isolated CMEMs and evaluate the surgical effect of hearing reconstruction. Methods: From January 2017 to January 2022, a retrospective study was performed on 36 patients (37 ears) with isolated CMEMs who all underwent endoscopic surgery. Demographic data, high-resolution computed tomography (HRCT) findings, intraoperative findings, surgical management and audiometric data were recorded. Results: Anomalies were categorized according to the Teunissen and Cremers classification system: 8 ears were categorized as class I, 8 ears as class II, 19 ears as class III and 2 ears as class IV. The air conduction pure tone average (AC-PTA) of 37 cases was 61.5 ± 8.6 dB preoperatively and 29.6 ± 6.9 dB postoperatively ( p  < 0.001). The mean preoperative air-bone gap (ABG) significantly decreased from 43.1 ± 8.7 dB to 12.8 ± 5.5 dB postoperatively. 36 of 37 cases (97%) met the criteria for successful operation. Conclusion: Isolated CMEMs are mainly manifested as aplasia of the stapes' superstructure and dysplasia of the long process of the incus. Transcanal endoscopic surgery seems a safe technique for the management of isolated CMEMs.